Problems of Ukraine’s integration into the joint aviation space of the EU - Жуков, І. А.; Долінце, Б. І.; Балакін, С. В. (Problems of Informatization and Management, 2020)
The paper considers the current situation in the air transportation market in Ukraine. It is shown that, in the Ukrainian segment of the global aviation market, the effectiveness of passenger traffic and air transportation in reference to passenger per kilometer may grow in national and international flight routes. An analysis of regulations governing all aspects of Ukraine’s integration into the common aviation space of the European Union has been made. The authors justify the rapid increase in civil aviation efficiency and high capability of the air transport industry of Ukraine, taking into account the global rates of civil aviation development. The main problems that may arise during the integration into the EU airspace are considered on the example of the countries that have ratified these agreements and are in the final stages of their implementation. An analysis of the negative consequences for domestic airlines, which with the high competitiveness of European low-cost carriers will lose a significant share of the airline market both over Ukraine and abroad. A comparison of the aircraft fleet of Ukrainian aircraft with major European airlines was made on the basis of their age and wear.The impact of the COVID-19 pandemic on the efficiency of passenger transportation and its consequences on the air transportation market in Ukraine is considered.